The Influence of Firm Size, Share Sales, and Inflation on Stock Prices in Companies Registered on The Jakarta Islamic Index - Chikita, Aninda Priska Ayu; Kartika, Metasari (Jurnal Ekonomi dan Perbankan Syariah, 2023)
Share price fluctuations can be analyzed through factors that can influence them, such as internal and external factors that can influence the company's share price. This research aims to analyze the influence of firm size, share sales, and inflation on share prices in companies listed on the Jakarta Islamic Index. This research was carried out by observing 10 companies registered on the Jakarta Islamic Index (JII), namely PT Adaro Energy Tbk, PT AKR Corporindo Tbk, PT Indofood CBP Sukses Makmur Tbk, PT Indo Tambangraya Megah Tbk, PT Kalbe Farma Tbk, PT Telkom Indonesia Tbk, PT Perusahaan Gas Negara Tbk, PT Bukit Asam Tbk, PT United Tractors Tbk, PT Unilever Indonesia Tbk. With a 10-year observation period, namely 2012-2021 using quarterly data. This research uses a panel data regression analysis method and is processed using the Eviews 12 application. The results of this research show that partially firm size has a positive and insignificant effect on stock prices, while share sales and inflation have a negative and significant effect on stock prices.